Patients’ safety: is there a systemic release of gentamicin by gentamicin-coated tibia nails in clinical use? - Moghaddam-Alvandi, Arash; Graeser, Viola; Westhauser, Fabian; Dapunt, Ulrike A.; Kamradt, Till; Wörner, Stefan M.; Schmidmaier, Gerhard (Therapeutics and clinical risk management, 2016)
Patients’ safety: is there a systemic release of gentamicin by gentamicin-coated tibia nails in clinical use? Arash Moghaddam,1 Viola Graeser,1 Fabian Westhauser,1 Ulrike Dapunt,1 Till Kamradt,1 Stefan M Woerner,2 Gerhard Schmidmaier1 1HTRG - Heidelberg Traume Research Group Center for Orthopedics, Trauma and Spinal Cord Injury, University Hospital Heidelberg, Heidelberg, Germany; 2Department of Internal Medicine and Clinical Chemistry, University Hospital Heidelberg, Heidelberg, Germany Introduction: Osteitis is one of the most serious complications in orthopedic surgery. Expert Tibia Nail (ETN) PROtect™ coated with a biodegradable layer of gentamicin-laden polymer was developed for prophylaxis of osteomyelitis. In systemic administration, gentamicin has only a small therapeutic index and serious side effects; it is potentially nephrotoxic as well as ototoxic. It is not yet known if relevant gentamicin concentrations are released into the systemic circulation after implantation of gentamicin-coated nails. In order to evaluate the patients’ risks profiles and increase patient safety, we measured gentamicin levels in pre- and postoperative serum samples of patients undergoing implantation of ETN PROtect.Methods: Twenty-five patients who received ETN PROtect between March 2012 and August 2014 were included in this study. Collection of blood samples occurred before the operation, at weeks 1-4, 3 and 6 months, and up to 1 year after the implantation. Measurement of gentamicin levels in serum samples was performed at the central laboratory of Heidelberg University Hospital. Additionally, laboratory parameters, C-reactive protein, leukocyte number, urea and creatinine concentrations were analyzed in routine controls before and after operating and assessed for systemic side effects.Results: Over the course of this prospective observational study, we were able to determine that gentamicin-coated nails do not release gentamicin into the systemic circulation above the lowest detectable level of 0.2 mg/dL. There were slight increases in the mean inflammation and renal retention markers, but no gentamicin-associated side effects could be linked to implantation. Furthermore, no allergic reactions could be detected during our study.Conclusion: Our findings suggest that there is no relevant release of gentamicin into the systemic circulation causing a systemic effect, and serious side effects due to gentamicin-coated tibia nails should not be feared. Postoperative monitoring of renal function does not seem necessary because of the implantation of ETN PROtect. Keywords: osteomyelitis, osteitis, pseudoarthrosis, fracture, therapy, ETN PROtect, implant, infection, tibia
Gesehen am 10.07.2020